2014
DOI: 10.1186/s12870-014-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, phylogenetic analysis, and expression profiling of endoplasmic reticulum molecular chaperone BiP genes from bread wheat (Triticum aestivum L.)

Abstract: BackgroundThe endoplasmic reticulum chaperone binding protein (BiP) is an important functional protein, which is involved in protein synthesis, folding assembly, and secretion. In order to study the role of BiP in the process of wheat seed development, we cloned three BiP homologous cDNA sequences in bread wheat (Triticum aestivum), completed by rapid amplification of cDNA ends (RACE), and examined the expression of wheat BiP in wheat tissues, particularly the relationship between BiP expression and the subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…BIP2 is a protein known for its role in preventing protein misfolding, facilitating protein folding and assembling protein bodies for subsequent transport from the endoplasmic reticulum to the cytoplasm (She et al ., ; Zhu et al ., ). We observed a slight upregulation of BIP2 at 21 and 28 DPA under high nitrogen availability.…”
Section: Discussionmentioning
confidence: 97%
“…BIP2 is a protein known for its role in preventing protein misfolding, facilitating protein folding and assembling protein bodies for subsequent transport from the endoplasmic reticulum to the cytoplasm (She et al ., ; Zhu et al ., ). We observed a slight upregulation of BIP2 at 21 and 28 DPA under high nitrogen availability.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the characterization of BiPs is a crucial contribution to the understanding of cellular, tissuespecific and developmentally related responses to ER stress. The BiP gene family has been investigated in several plant species, including Arabidopsis, rice, wheat, pepper and citrus 36,37,[41][42][43][44] . In addition, there are several historic and recent studies using transgenic lines overexpressing various BiPs to characterize their roles in plant tolerance to adverse environmental conditions or demonstrating some evidence for tissue specific regulation 6,15,32,36,43,45 .…”
Section: Discussionmentioning
confidence: 99%
“…The UPR-related elements were previously identified in the AtBiP promoters 36,37 . Here we identify the UPR element II (UPRE-II), UPRE-III, ER stress-response element I (ERSE-I) and…”
Section: Stbip Promoters Are Enriched With Developmental and Stress-rmentioning
confidence: 98%
See 1 more Smart Citation
“…Hurkman et al (2009) also found that PDI had very abundant content at early stages of grain development. More recently, Zhu et al (2014b) has demonstrated that TaBip has the highest expression level at 14 DPA. The high expression of those molecular chaperones along with the rapid accumulation rate of 1Dx5 + 1Dy10 subunits at early grain development stages could facilitate the folding of gluten proteins and help to bring about the formation of more regular gluten polymers, which might result in superior gluten quality.…”
Section: Discussionmentioning
confidence: 99%